Design of uncertainty and disturbance estimator based tracking control for fuzzy switched systems. Issue 14 (16th June 2021) - Sakthivel, R.; Harshavarthini, S.; Almakhles, Dhafer J.; Kavikumar, R.
Abstract: In this paper, an uncertainty and disturbance estimator (UDE)‐based control is employed to ensure the finite‐time tracking and disturbance rejection performance for a class of Takagi–Sugeno fuzzy switched systems including additive time‐varying delays, unknown time‐varying uncertainties and disturbances. To be precise, the robust tracking performance is achieved by estimating unknown uncertainties and disturbances with the aid of low‐pass filter by means of appropriate bandwidth choice of the desired filter. Moreover, a new delay‐dependent finite‐time stability criterion is derived by employing fuzzy‐dependent Lyapunov–Krasovskii functional, extended Wirtinger's integral inequality and average dwell‐time approach to enforce the addressed system to track the given reference system within a finite period of time. Finally, the developed theoretical results are ensured by presenting the numerical examples with simulation results.